2D CFD Simulation on the Aerodynamic Performance Enhancement of H-Darrieus VAWT Utilized with Flaps - Yamin, Mohamad; Putra, Andrian; Firmansyah, Riyan (Engineering Science Letter, 2024)
This research aims to enhance the aerodynamic performance of the H-Darrieus Vertical Axis Wind Turbine (VAWT) consisting of 3 main blades with the addition of flaps on each blade. Performance evaluation and geometry optimization are conducted by varying the gap distance between the main blades and flaps and altering the deflection angle of the flaps. A numerical approach using Computational Fluid Dynamics (CFD) is employed to analyze the performance of VAWT turbines and optimize the gap distance between the blades and flaps. NACA 0018 profiles are utilized for the main blades, while NACA 0015 profiles are used for the flaps. A two-dimensional CFD model of the VAWT turbine is analyzed using the Unsteady Reynolds Averaged Navier-Stokes (URANS) method with the k-ω Shear Stress Transport (SST k-ω) turbulence model. Simulations are conducted using ANSYS Fluent software, encompassing turbine models with and without flaps—validation of simulation results for turbines with and without flaps through experimental and numerical approaches. Simulation variations with flaps are carried out by considering the parameter of gap distance between the blades and flaps at various Tip Speed Ratio (TSR) values. The research results indicate an optimal distance between the main blades and flaps at a specific flap deflection angle where the power coefficient reaches its maximum value. Overall, the addition of flaps and deflection angle variations positively contribute to the aerodynamic performance of VAWT turbines.